SINTESIS PERAK NANOPARTIKEL MELALUI REDUKSI SPONTAN MENGGUNAKAN REDUKTOR ALAMI EKTRAK KULIT LEMON SERTA KARAKTERISASINYA SEBAGAI ANTIFUNGI DAN ANTIBAKTERI - Widya Ernayati Kosimaningrum; Alia Badra Pitaloka; Afif Sena Hidayat; Wahidatun Aisyah; Syahrul Ramadhan; Malik Abdul Rosyid (JURNAL INTEGRASI PROSES, 2020)
Silver nanoparticle, Ag0, is a broad spectrum antimicrobial agent with a very low risk of resistance. In this study, silver nanoparticles, Ag0, were synthesized through the spontaneous reduction of Ag + solution using a natural reducing agent of lemon peel extract. Extraction was carried out at 60oC for 10 minutes in a water solvent. The extraction of lemon peel involves varying the mass of the lemon peel powder, namely 2.5; 5; 7.5; and 10 grams to produce varying concentrations of reducing agents. Synthesis of silver nanoparticles was carried out at 60oC for 20 minutes by mixing 0.1 M Ag + solution with the extract solution with various concentrations. The result of the synthesis is a dark brown to blackish colloidal solution which indicates the formation of Ag0 from micro to nanoparticles in the solution. The concentration of lemon peel extract is directly proportional to the amount of Ag0 formed, which is characterized by the colour of the solution. The Ag0 solution showed its effectiveness as an antifungal under five days of observation. The Ag0 solution also exhibits highly effective antibacterial properties based on testing against E. coli. ‘